Damping performance optimization of the magnetorheological damper with three parallel channels. (October 2022) - Zhu, Zhuangguo; Zhang, Xiaobing
Abstract: In existing magnetorheological dampers (MRD) under impact load of launching devices, there is a contradiction between output damping force and adjustable coefficient of damping force, which is hard to cope with the harsh working conditions. To solve this problem, a new structure of three-channel MRD is proposed. The piston head is equipped with individually controllable coils and parallel three annular channels distributed on both sides of the coils. This damper greatly increases the output damping force of the three-channel MRD with ensuring a large adjustable coefficient of damping force. The multi-physical field of the damper is simulated, and damping performance of the damper under different excitation currents and single coil control is simulated. The influence of the radial position of the damping channels on the damping performance of the damper is investigated. It is demonstrated from the results that the closer of the damping channels is, the larger the output damping force of the damper is, and the maximum output damping force is 1881 N, which is 5.69 % higher than that of the existing three-channel damper. This work provides a new idea for making full use of multi-coil and multi-channel MRD structure and improving damping performance of MRD.